2021
DOI: 10.1097/md.0000000000023966
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety evaluation of hyperbaric oxygen therapy for patients with ulcerative colitis

Abstract: Background: Ulcerative colitis (UC) belongs to chronic colitis whose etiology and pathogenesis still have remained unclear. Hyperbaric oxygen therapy (HBOT) has been demonstrated to be effective for UC therapy. Still, evidence of its efficacy and safety is inconclusive. The purpose of the protocol is to evaluate the efficacy and safety of HBOT in UC therapy. Methods: This systematic review will retrieve studies that meet the requirements in Embase, MEDL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…For instance, a phase 2A clinical trial demonstrated the possible benefits from HBOT in combination with steroids for patients with ulcerative colitis in terms of achieving higher rates of clinical remission, and a reduced probability of progression to second-line therapy during the hospitalization [ 61 ]. However, there are few studies in this field, and soon an updated meta-analysis and systematic review of the available evidence will be published [ 62 ]. Similar conclusions might be extrapolated to radiation-induced hemorrhagic cystitis and proctitis [ 63 ].…”
Section: Approved Indications For Hbotmentioning
confidence: 99%
“…For instance, a phase 2A clinical trial demonstrated the possible benefits from HBOT in combination with steroids for patients with ulcerative colitis in terms of achieving higher rates of clinical remission, and a reduced probability of progression to second-line therapy during the hospitalization [ 61 ]. However, there are few studies in this field, and soon an updated meta-analysis and systematic review of the available evidence will be published [ 62 ]. Similar conclusions might be extrapolated to radiation-induced hemorrhagic cystitis and proctitis [ 63 ].…”
Section: Approved Indications For Hbotmentioning
confidence: 99%
“…Thirteen studies were finally included for statistical analysis. [13][14][15][16][17][18][19][20][21][22][23][24][25] Characteristics of the articles All included studies were RCTs. A total of 780 patients were included with 397 patients in the intervention group (Tables 1 and 2).…”
Section: Literature Search and Selectionmentioning
confidence: 99%
“…Although these Chinese studies did not describe the exact requirement of disease flares, some studies have provided detailed data about the disease severity of their enrolled patients. For example, Liang 13 included 15 patients (seven patients in the intervention group) with mild disease and 15 patients (eight patients in the intervention group) with moderate disease. Shen 14 included nine patients (three patients in the intervention group) with mild disease, 14 patients (four patients in the intervention group) with moderate disease, and two patients (one patient in the intervention group) with severe disease.…”
Section: Literature Search and Selectionmentioning
confidence: 99%
See 1 more Smart Citation